Eryptosis as a New Insight in Malaria Pathogenesis - Scovino, Aline Miranda; Totino, Paulo Renato Rivas; Morrot, Alexandre (Frontiers in Immunology, 2022)
Eryptosis is programmed cell death that occurs in red blood cells. Despite being anucleated cells, there are similarities between eryptosis and apoptosis, such as increased calcium efflux, calpain activation, phosphatidylserine exposure, and cell blebbing and cell shrinkage. Eryptosis occurs physiologically in red blood cells, as a consequence of the natural senescence process of these cells, but it can also be stimulated in pathological situations such as metabolic syndromes, uremic syndromes, polycythemia vera, anemias such as sickle cell anemia and thalassemia, and infectious processes including Plasmodium infection. Infection-induced eryptosis is believed to contribute to damage caused by plasmodium, but this is still widely discussed in the literature. In this review we will provide an overeview of eryptosis mechanisms and its possible pathogenic role in malaria.